Greening Arab American University-Jenin - Yousef, AbuShanab; Mo’ath, Arqawi; Muhammad, Juma’a; Muhammad, Mashaqi (My University, 2018)
Due to the increased amount of needed electricity every year in Arab American University-Jenin and the expensive electricity bill, a goal has been set up to achieve a lower cost bill. This study aims to install of Photovoltaic (PV) systems in (AAUJ). This project begins with feasibility study of 1-MW grid-conducted solar PV system, technical and financial performances of PV system. The preliminary analysis of the results shows that the project is useful. PV system is to be developed and connected to the existing electrical grid (grid-connected PV system) to feed the produced electrical power directly to the grid through appropriate dc to ac inverters.